Book Launch, "Transforming Food Systems for a Rising India" - Pingali, Prabhu; Aiyar, Anaka; Abraham, Mathew; Rahman, Andaleeb (2019)
Prabhu Pingali, Anaka Aiyar, Mathew Abraham, and Andaleeb Rahman BOOK LAUNCH Transforming Food Systems for a Rising India JUN 6, 2019 - 12:15 PM TO 01:45 PM EDT